Real time FPGA Implementation of PWM Chopper Fed Capacitor Run Induction Motor - N. Murali; V. Balaji (Institute of Advanced Engineering and Science, 2018)
This paper presents the performance enhancement of capacitor run induction motor by pulse width modulated AC chopper.The phase angle control faces severe shortfall in the performance improvement for larger triggering angles. In this paper the comparison of phase angle control and sinusoidal pulse width modulation technique is encountered for effective speed control of single phase capacitor run induction motor. The necessary parameters are taken into considerations are higher efficiency, lesser total harmonic distortion and high input power factor. The results are compared by using the simulations using matlab Simulink environment. The validation of result in hardware is implemented using Field programmable gate array for sinusoidal pulse width modulation technique.